Electrolyte containing multifunctional additive for aqueous zinc ion battery

By adding multifunctional additives such as polyethylene glycol p-isooctylphenyl ether to the aqueous zinc ion battery electrolyte, the problems of zinc dendrites growth, hydrogen evolution and zinc negative electrode corrosion are solved, and the cycle stability of the battery and the reversibility of zinc negative electrode are improved.

CN119786762APending Publication Date: 2025-04-08ANHUI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510074370.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Water-based zinc ion batteries have problems such as uncontrollable growth of zinc dendrites, corrosion of hydrogen evolution and zinc negative electrodes, resulting in short battery cycle life and poor stability.

Method used

Polyethylene glycol p-isooctylphenyl ether and/or polyethylene glycol p-isooctyl fluorinated p-phenyl ether are used as multifunctional additives for the electrolyte. Through the combination of its hydrophilic and hydrophobic groups, the deposition behavior of zinc ions is optimized and an electrostatic shielding layer is formed to inhibit the growth of zinc dendrites.

Benefits of technology

Effectively promote the uniform deposition of zinc ions, reduce hydrogen evolution and corrosion reactions, and significantly improve the reversibility of zinc negative electrodes and the cycling stability of aqueous zinc ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786762A_ABST
    Figure CN119786762A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of aqueous zinc ion batteries, and particularly discloses an aqueous zinc ion battery electrolyte containing a multifunctional additive, the electrolyte is composed of a water-soluble zinc salt, deionized water and an additive, and the additive is polyethylene glycol p-isooctyl phenyl ether and / or polyethylene glycol p-isooctyl fluorinated phenyl ether. The additive can form a hydrophobic protection layer on the outer surface of the Zn negative electrode, so that side reactions such as hydrogen evolution and corrosion are inhibited, the additive can accelerate desolvation kinetics of zinc ions, promote uniform deposition of zinc and effectively improve reversibility of the Zn negative electrode, and meanwhile, the rate capability and the cycle performance of the aqueous zinc ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aqueous zinc ion batteries, and in particular relates to an electrolyte for aqueous zinc ion batteries containing a multifunctional additive. Background Art

[0002] With the continuous consumption of fossil energy and the increasingly serious environmental pollution problem, clean energy will become the main source of energy for people, but the current mainstream clean energy, whether wind or solar, has uncertainty in the power generation process. Lithium-ion batteries have the characteristics of high energy density and scalability, and are considered to be the most promising electrochemical energy storage equipment. However, due to the scarcity of lithium resources and the safety hazards caused by the flammability of its organic electrolyte, its further large-scale sustainable development is limited. In contrast, aqueous zinc-ion batteries are considered to be one of the most promising alternatives to lithium-ion batteries due to their high theoretical capacity, abundant resources, low cost and high safety. However, aqueous zinc-ion batteries are currently in the research and development stage, and their practical application faces many problems, such as: the uncontrollable growth of zinc dendrites may pierce the diaphragm, causing battery short circuit; side reactions such as hydrogen evolution and corrosion will cause battery volume expansion and short cycle life.

[0003] To solve the above problems, researchers have adopted a series of improvement schemes, mainly including electrolyte additives, zinc negative electrode surface modification and protection, diaphragm modification, etc. Among them, electrolyte additives have attracted widespread attention from researchers due to their advantages such as simplicity, effectiveness and low cost. Currently, commonly used electrolyte additives are mainly divided into organic additives and metal ion additives. Organic additives mainly optimize the deposition behavior of zinc ions by adsorbing on the surface of zinc negative electrode, thereby effectively promoting the uniform deposition of zinc ions. Metal ion additives can inhibit the growth of zinc dendrites to a certain extent by adsorbing on the surface of zinc electrode to form a positively charged electrostatic shielding layer. However, the uniform dissolution of organic additives in aqueous electrolytes, hydrogen evolution and corrosion of zinc electrodes are also not to be ignored. Therefore, it is very important to design and develop an electrolyte additive that can solve the above problems of aqueous zinc ion batteries at the same time. Summary of the invention

[0004] The purpose of the present invention is to provide an electrolyte for an aqueous zinc ion battery containing a multifunctional additive, so as to solve the technical problems of hydrogen evolution, zinc negative electrode corrosion and uncontrollable growth of zinc dendrites in existing aqueous zinc ion batteries, and to improve the reversibility of the zinc negative electrode during the cycle and the cycle stability of the aqueous zinc ion battery.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme:

[0006] The invention provides an aqueous zinc ion battery electrolyte containing a multifunctional additive. The electrolyte consists of a water-soluble zinc salt, deionized water and the additive. The additive is polyethylene glycol p-isooctylphenyl ether and / or polyethylene glycol p-isooctyl fluorinated phenyl ether.

[0007] Furthermore, in the electrolyte, the concentration of the water-soluble zinc salt is 0.1-3.0 mol / L, and the concentration of the additive is 1-100 mmol / L. -1 .

[0008] Furthermore, the water-soluble zinc salt is at least one of zinc sulfate, zinc acetate, zinc trifluoromethanesulfonate, zinc chloride and zinc perchlorate.

[0009] The method for preparing the electrolyte for aqueous zinc ion batteries of the present invention comprises the following steps:

[0010] Step 1: dissolving a water-soluble zinc salt in deionized water to obtain a basic electrolyte;

[0011] Step 2: Add additives to the basic electrolyte, stir until completely dissolved, and let stand to obtain an aqueous zinc ion battery electrolyte containing a multifunctional additive.

[0012] The present invention further provides an aqueous zinc ion battery, wherein the electrolyte of the aqueous zinc ion battery adopts the electrolyte containing the multifunctional additive.

[0013] The aqueous zinc ion battery can be a symmetrical battery, a half-cell or a full battery.

[0014] Furthermore, the symmetrical battery is composed of zinc foil, a glass fiber separator and the electrolyte containing the multifunctional additive.

[0015] Furthermore, the half-cell is composed of zinc foil, glass fiber separator, copper foil and the electrolyte containing the multifunctional additive.

[0016] Furthermore, the full battery consists of a zinc foil negative electrode, a glass fiber separator, a polyaniline, I2, manganese dioxide or vanadium pentoxide positive electrode and an electrolyte containing a multifunctional additive.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) The present invention uses polyethylene glycol p-isooctylphenyl ether and / or polyethylene glycol p-isooctyl fluorinated phenyl ether as a multifunctional additive for an aqueous zinc ion battery electrolyte, wherein one end of the additive contains a hydrophilic group and the other end contains a hydrophobic group. The lone pair of electrons carried in the ether bond of the hydrophilic end has a strong zinc affinity, and is preferentially adsorbed on the surface of the Zn negative electrode, serving as a zinc affinity nucleation site, inducing uniform deposition of zinc ions; while the trimethyl group at the hydrophobic end exposes the outer surface of the Zn negative electrode, forming a hydrophobic protective layer, thereby reducing direct contact between active water molecules and the zinc negative electrode, and inhibiting side reactions such as hydrogen evolution and corrosion.

[0019] (2) The present invention uses polyethylene glycol p-isooctylphenyl ether and / or polyethylene glycol p-isooctyl fluorinated phenyl ether as a multifunctional additive for aqueous zinc ion battery electrolyte. The benzene ring in the additive has a conjugated effect with the adjacent oxygen atom, and the steric hindrance effect of the hydrophobic end trimethyl group helps to expand the Zn 2+ The solvation sheath structure weakens the Zn 2+ The interaction between Zn and H2O accelerates the desolvation kinetics of Zn ions, promotes the uniform deposition of Zn, effectively improves the reversibility of the Zn negative electrode, and at the same time improves the rate performance and cycle performance of aqueous Zn-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 FTIR spectra of the electrolytes obtained in the embodiments and comparative examples;

[0021] Figure 2 The Zn / / Zn symmetric battery assembled with the electrolytes obtained in the embodiments and comparative examples was -2 Cyclic voltage curves under current density;

[0022] Figure 3 Comparative Example 1 ( Figure 3 (a)) and Example 2 ( Figure 3 The Zn / / Zn symmetric cell assembled with the electrolyte in (b) is 1 mA cm -2 and 1mAh cm -2 Scanning electron microscope (SEM) image of the zinc anode after 30 cycles;

[0023] Figure 4 2 is the chronoamperometric (CA) curve of the Zn / / Zn symmetric battery assembled with the electrolytes obtained in the embodiments and comparative examples;

[0024] Figure 5 2 is the coulombic efficiency curve of the Zn / / Cu half-cell assembled using the electrolytes of Comparative Example 1 and Example 2;

[0025] Figure 6It is the cycle performance curve of the full battery assembled using the electrolytes of Comparative Example 1 and Example 2. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions of the present invention are further explained in conjunction with specific embodiments below. The following embodiments are implemented on the premise of the technical solutions of the present invention, and detailed implementation methods and specific operating processes are given, but the protection scope of the present invention is not limited to the following embodiments.

[0027] Example 1

[0028] In this embodiment, the aqueous zinc battery electrolyte is prepared according to the following steps:

[0029] Step 1: dissolving water-soluble zinc trifluoromethanesulfonate powder in deionized water to obtain a basic electrolyte;

[0030] Step 2: Add polyethylene glycol p-isooctylphenyl ether (Triton X-100) additive to the basic electrolyte, stir at 800 rpm for 2 h, and let stand for 12 h to obtain a multifunctional electrolyte in which the concentration of zinc trifluoromethanesulfonate is 3 mol L -1 The concentration of polyethylene glycol 4-isooctylphenyl ether was 16 mmol L -1 .

[0031] Example 2

[0032] In this embodiment, a multifunctional electrolyte for aqueous zinc batteries is prepared according to the following steps:

[0033] Step 1: dissolving water-soluble zinc trifluoromethanesulfonate powder in deionized water to obtain a basic electrolyte;

[0034] Step 2: Add polyethylene glycol p-isooctylphenyl ether (Triton X-100) additive to the basic electrolyte, stir at 800 rpm for 2 h, and let stand for 12 h to obtain a multifunctional electrolyte in which the concentration of zinc trifluoromethanesulfonate is 3 mol L -1 The concentration of polyethylene glycol 4-isooctylphenyl ether was 32 mmol L -1 .

[0035] Example 3

[0036] In this embodiment, a multifunctional electrolyte for aqueous zinc batteries is prepared according to the following steps:

[0037] Step 1: dissolving water-soluble zinc trifluoromethanesulfonate powder in deionized water to obtain a basic electrolyte;

[0038] Step 2: Add polyethylene glycol p-isooctylphenyl ether (Triton X-100) additive to the basic electrolyte, stir at 800 rpm for 2 h, and let stand for 12 h to obtain a multifunctional electrolyte in which the concentration of zinc trifluoromethanesulfonate is 3 mol L -1 The concentration of polyethylene glycol 4-isooctylphenyl ether was 64 mmol L -1 .

[0039] Comparative Example 1

[0040] The electrolyte provided in this comparative example is a basic electrolyte obtained by dissolving zinc sulfate heptahydrate powder in deionized water, wherein the concentration of zinc trifluoromethanesulfonate is 3 mol L -1 .

[0041] In order to test the practical performance of the electrolytes prepared in the above embodiments and comparative examples, batteries were assembled and battery performance tests were performed according to the following method:

[0042] Put the zinc sheet into the positive electrode shell, add appropriate amount of electrolyte, then put in the glass fiber separator. After adding appropriate amount of electrolyte, stack the zinc negative electrode, gasket and shrapnel in sequence, cover the negative electrode shell, and finally put it into the button battery packaging machine to seal it into a symmetrical battery.

[0043] Figure 1 1 is the Fourier transform infrared (FTIR) spectrum of different electrolytes. Compared with the conventional electrolyte of Comparative Example 1, the FTIR spectrum of the electrolytes obtained in Examples 1, 2, and 3 is located at 3100-3400 cm -1 The OH stretching vibration shifts to a higher wavenumber, indicating that the addition of polyethylene glycol-p-isooctylphenyl ether additive to the conventional electrolyte weakens the hydrogen bonding between water molecules, thereby reducing the activity of water molecules and inhibiting the hydrogen evolution reaction.

[0044] Figure 2 The Zn / / Zn symmetric battery assembled with different electrolytes has a high performance at 1 mA cm -2 Cyclic voltage curve under current density. It can be concluded from the figure that the cycle life of the Zn / / Zn symmetric battery assembled with the electrolyte containing polyethylene glycol 4-isooctylphenyl ether additive exceeds 3000 hours, while the cycle life of the Zn / / Zn symmetric battery assembled with the conventional electrolyte is less than 100 hours.

[0045] Figure 3 Comparative Example 1 ( Figure 3 (a)) and Example 2 ( Figure 3 The Zn / / Zn symmetric cell assembled with the electrolyte in (b) is 1 mA cm -2 and 1mAh cm -2The scanning electron microscope (SEM) image of the zinc negative electrode after 30 cycles. The results show that the surface of the zinc sheet using the electrolyte containing polyethylene glycol-p-isooctylphenyl ether in Example 2 is smooth and no obvious dendrites appear, while the surface of the zinc sheet using the conventional electrolyte in Comparative Example 1 forms randomly distributed flaky byproducts.

[0046] Figure 4 The chronoamperometric (CA) curves of Zn / / Zn symmetric cells assembled with different electrolytes. The current density of the Zn / / Zn symmetric cell assembled with conventional electrolyte continued to increase rapidly, while the current density of the Zn / / Zn symmetric cell assembled with electrolytes containing different concentrations of polyethylene glycol-p-isooctylphenyl ether additives stabilized after a short nucleation process of 10s, entering a stable and continuous three-dimensional diffusion process. The stable low current density means that the zinc deposition is uniform, and the fast ion transport power will reduce the diffusion polarization, thereby having a good regulatory effect on zinc deposition.

[0047] Commercial zinc foil was used as the negative electrode, commercial copper foil was used as the positive electrode, and the electrolytes of Comparative Example 1 and Example 2 were used to assemble Zn / / Cu half-cells, respectively. Figure 5 is the Coulombic efficiency curve of the assembled Zn / / Cu half-cell. Figure 5 It can be seen that the Zn / / Cu half-cell assembled with the electrolyte added with polyethylene glycol-p-isooctylphenyl ether exhibits more stable cycling performance at 2 mA cm -2 The Zn / / Cu half-cell assembled with conventional electrolyte can be stably cycled for about 900 times at a current density of 2 mA cm -2 When the cycle number was less than 90 times at the current density, the curve showed extremely unstable fluctuations, which meant that a short circuit occurred inside the battery.

[0048] Commercial zinc foil was used as the negative electrode and I2 was used as the positive electrode, and full batteries were assembled using the electrolytes of Comparative Example 1 and Example 2, respectively. Figure 6 is the cycle performance curve of the assembled full battery. Figure 6 It can be seen that the full battery assembled with the electrolyte added with polyethylene glycol isooctylphenyl ether still has a high capacity retention rate after 4000 cycles; while the full battery assembled with conventional electrolyte shows obvious capacity attenuation after 100 cycles, and the final capacity retention rate is only about 20%.

[0049] From the above content, it can be seen that the multifunctional electrolyte additive provided by the present invention can optimize the deposition behavior of zinc ions, thereby effectively promoting the uniform deposition of zinc ions. The additive can also be adsorbed on the surface of the zinc electrode to form a positively charged electrostatic shielding layer, which can inhibit the growth of zinc dendrites to a certain extent, thereby effectively solving the problems of zinc dendrites, zinc metal corrosion and hydrogen evolution, and greatly improving the cycle performance of the zinc negative electrode.

[0050] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art will easily understand that the above are only preferred examples of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An aqueous zinc ion battery electrolyte containing a multifunctional additive, characterized in that: The electrolyte consists of water-soluble zinc salt, deionized water and additives, and the additive is polyethylene glycol p-isooctylphenyl ether and / or polyethylene glycol p-isooctyl fluorinated phenyl ether.

2. The aqueous zinc ion battery electrolyte according to claim 1, wherein In the electrolyte, the concentration of the water-soluble zinc salt is 0.1-3.0 mol / L, and the concentration of the additive is 1-100 mmol / L.

3. The aqueous zinc ion battery electrolyte according to claim 1, wherein The water-soluble zinc salt is at least one of zinc sulfate, zinc acetate, zinc trifluoromethanesulfonate, zinc chloride and zinc perchlorate.

4. A method for preparing an aqueous zinc ion battery electrolyte according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: dissolving a water-soluble zinc salt in deionized water to obtain a basic electrolyte; Step 2: Add additives to the basic electrolyte, stir until completely dissolved, and let stand to obtain an aqueous zinc ion battery electrolyte containing a multifunctional additive.

5. An aqueous zinc ion battery, characterized in that: The electrolyte according to any one of claims 1 to 3 is used.

Citation Information

Patent Citations

  • Preparation method of polyaniline / carbon composite material for cathode material of aqueous zinc ion battery

    CN110854365A

  • Aqueous electrolyte of zinc metal battery

    CN115566281A

  • Electrolytic solution for zinc battery and zinc battery

    JP2021180116A